Rove Beetles of the Genera Agaricochara, Brachida, and Encephalus (Coleoptera, Staphylinidae, Aleocharinae) of Ukraine - Glotov, S.V. (Вестник зоологии, 2012)
Three genera, Agaricochara Kraatz, 1856, Brachida Mulsant et Rey, 1871, and Encephalus Stephens, 1832 represented in Ukrainian fauna by one species each are reviewed. Detailed diagnoses and descriptions, peculiarities of biology and geographical distribution are given for each species fnd genera. New synonymy is established: Brachida exigua (Heer, 1839) = Brachida kraatzii Hochhuth, 1872 syn. n.